Strategi Komunikasi Guru Dalam Upaya Meningkatkan Proses Pembelajaran Siswa SDN Tebet Barat 01 Jakarta Selatan Di Masa Pandemi Covid -19 - Gan Gan Giantika (Jurnal Komunikasi, 2020)
Abstract - Communication in education carried out by teachers and students is not only the process of exchange and delivery of learning material, but there is a dimension of teacher and student relations being the main requirements for the creation of an effective learning process. A good teacher is a good communicator or an effective teacher is an effective communicator in the delivery of learning materials, but since December 2019, with the Covid - 19 pandemic outbreak throughout the country that resulted in death in sufferers and this disease is transmitted quickly has an impact on the world of education in Indonesia therefore needs to implement an appropriate communication strategy in the delivery of learning material in the 19th Pandemic era. This study aims to reveal the Teacher Communication Strategies in Efforts to Improve Student Learning Processes in Tebet Barat 01 South Jakarta Elementary School In the Covid Pandemic Period -19. The method used by researchers in this study is descriptive qualitative research methods. In this study produced a Teacher Communication Strategies in Efforts to Improve Student Learning Processes in Tebet Barat 01 South Jakarta Elementary School In the Covid Pandemic Period -19by using online and social media communication media, namely zoom and whatsapp. The conclusion of this research is that with the communication strategy with the media zoom and whatsapp carried out by the teacher SDN Tebet Barat 01 South Jakarta, the learning objectives can be achieved, namely printing and directing students to be good people, good personality and smart as well as maintaining the safety and health of the inner and outer students, teachers , the principal of the school and all citizens in the area of the teaching unit.Keywords: Communication Strategy, Learning Process